Intralesional and subarachnoid bleeding of a spinal schwannoma presenting with acute cauda equina syndrome. Issue 7 (12th July 2019) - Dobran, Mauro; Nasi, Davide; Della Costanza, Martina; Formica, Francesco
Abstract : We present an unusual case of spinal neurinoma with intralesional and subarachnoid bleeding with acute cauda equina syndrome. A 38-year-old man was admitted to our department after a minor thoracic spinal trauma with right lower limb plegia and urinary retention. MRI showed a T11 intradural tumour with intralesional and subarachnoid haemorrhage. The patient was operated of spinal cord decompression and complete tumour resection. The histological examination documented a schwannoma with large haemorrhagic intratumoural areas. A full neurological recovery was documented at 6-month follow-up.